2017
DOI: 10.4103/tjo.tjo_15_17
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable suture strabismus surgery in pediatric patients using pull-string technique

Abstract: BACKGROUND/PURPOSE:The concept of adjustable suture has been developed in strabismus surgeries for nearly four decades. This technique is not yet universally embraced by strabismus surgeons, especially in pediatric patients. The aim of this study is to describe and evaluate the application of the adjustable suture with pull-string technique in pediatric patients.METHODS:A retrospective medical record review was conducted for patients aged 18 years and under who received adjustable suture strabismus surgery usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The definition of success in strabismus surgery varies among different studies. Most studies set their success criteria as 8 to 10 PD deviations from orthophoria at either the 3-month, 6-month or last follow-up (8,9,12,15,(21)(22)(23)(24). Kushner et al (25) found that orthotropia in infants at their 6-month postoperative visits was more related to better visual function outcomes 5 years later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of success in strabismus surgery varies among different studies. Most studies set their success criteria as 8 to 10 PD deviations from orthophoria at either the 3-month, 6-month or last follow-up (8,9,12,15,(21)(22)(23)(24). Kushner et al (25) found that orthotropia in infants at their 6-month postoperative visits was more related to better visual function outcomes 5 years later.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to most adjustments that could be made in the office only by local anesthetics, adjustments in children seem to be more challenging and painful for both the patients and their parents despite some alternatives in anesthetics ( 9 ). To improve the success rate in pediatric strabismus surgery, certain alternative procedures are combined with strabismus surgeries, such as botulinum toxin A injection ( 10 , 11 ) and pull-string adjustments ( 12 ). However, a need for additional procedures cannot be avoided ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The definition of success in strabismus surgery varies depending on the study and the patient group. The most accepted success criterion across horizontal strabismus studies is 8-10 PD misalignment at either the 3-month, 6-month, or final follow-up [19,25,[28][29][30][31][32][33]. In consecutive strabismus after orbital fracture reconstruction surgery, few studies have achieved a consensus on postoperative success criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Such protocols have further expanded the availability of adjustable sutures for pediatric patients. [10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%